Artificial extracellular matrices support cell growth and matrix synthesis of human dermal fibroblasts in macroporous 3D scaffolds. (26th May 2015) - van der Smissen, Anja; Hoffmeister, Peter‐Georg; Friedrich, Nadja; Watarai, Akira; Hacker, Michael C.; Schulz‐Siegmund, Michaela; Anderegg, Ulf
Abstract: Surface modification of materials designed for regenerative medicine may improve biocompatibility and functionality. The application of glycosaminoglycans (GAGs) and chemically sulphated GAG derivatives is a promising approach for designing functional biomaterials, since GAGs interact with cell‐derived growth factors and have been shown to support fibroblast growth in two‐dimensional (2D) cultures. Here, coatings with artificial extracellular matrix (aECM), consisting of the structural protein collagen I and the GAG hyaluronan (HA) or sulphated HA derivatives, were investigated for their applicability in a three‐dimensional (3D) system. As a model, macroporous poly(lactic‐co‐glycolic acid) (PLGA) scaffolds were homogeneously coated with aECM. The resulting scaffolds were characterized by compressive moduli of 0.9–1.2 MPa and pore sizes of 40–420 µm. Human dermal fibroblasts (dFbs) colonized these aECM‐coated PLGA scaffolds to a depth of 400 µm within 14 days. In aECM‐coated scaffolds, collagen I ( α1 ) and collagen III ( α1 ) mRNA expression was reduced, while matrix metalloproteinase‐1 ( MMP‐1 ) mRNA expression was increased within 7 days, suggesting matrix‐degradation processes. Stimulation with TGF β 1 generally increased cell density and collagen synthesis, demonstrating the efficiency of bioactive molecules in this 3D model. Thus, aECM with sulphated HA may modulate the effectivity of TGF β 1‐induced collagen I( α 1) expression, as demonstrated previously in 2D systems. Overall, the tested aECM with modified HA is also a suitable material for fibroblast growth under 3D conditions. Copyright © 2015 John Wiley & Sons, Ltd.